Composite asphalt binder modification with waste Non-tire automotive rubber and pyrolytic oil. (2022) - Kumar, Ankush; Choudhary, Rajan; Kumar, Abhinay
Abstract: Ethylene-propylene-diene monomer (EPDM) rubber is a synthetic rubber having a share of about one-half of the total consumption of non-tire automotive rubber parts such as weather strips, window seals, hoses, etc . Pyrolysis is gaining attention as a thermochemical route for the effective and sustainable treatment of end-of-life tires. Tire pyrolytic oil (TPO) is one of the principal products generated from the pyrolysis of scrap tires. This study evaluated the use of TPO and EPDM waste rubber in composite asphalt binder modification through rheological characterization. In addition, the study also compared two processes (with and without pre-treatment/premixing of TPO and EPDM) for the preparation of the composite modified asphalt binders. The high temperature rheological characterization of binders was executed by the Superpave rutting criterion, failure temperatures, and multiple stress creep and recovery (MSCR) test. Frequency sweeps were conducted at multiple temperatures to study the changes in complex modulus and phase angle master curves. Also, the frequency sweep data was employed for analyzing the viscoelastic behavior of binders through storage and loss moduli crossover response. Furthermore, rheological tests including Superpave fatigue parameter, linear amplitude sweep (LAS), and binder yield energy test (BYET) were conducted at intermediate temperatures on the long-term aged binders. The observed results suggested an improvement in the asphalt binder performance with the composite modification in comparison to the single modification with EPDM and TPO alone. Pre-mixing of TPO and EPDM before adding to asphalt binder proved to be a better approach for preparing composite modified binder with EPDM rubber and TPO, and yielded better high- and intermediate-temperature performance.